Underreporting of drug use among electronic dance music party attendees - Palamar, Joseph J. (Clin Toxicol (Phila), 2020)
BACKGROUND AND OBJECTIVES: Electronic dance music (EDM) party attendees are at high risk for drug use. However, little is known regarding the extent of underreporting of drug use in this population, in part, because use of synthetic drugs is often associated with unknown exposure to adulterant drugs. We estimated the extent of underreported drug use in this population by comparing self-reported use to hair toxicology results. METHODS: Time-space sampling was used to survey adults entering EDM events at nightclubs and dance festivals in New York City from January through August of 2019. Seven hundred ninety-four adults were surveyed and 141 provided analyzable hair samples. We queried past-year use of >90 drugs and tested hair samples using ultra-high performance liquid chromatography-tandem mass spectrometry. We compared hair test results to past-year self-reported use and adjusted prevalence estimates by defining use as reporting use or testing positive. Correlates of discordant reporting, defined as testing positive after not reporting use, were estimated. RESULTS: Prevalence of drug use increased when considering positive hair tests in estimates, with 43.8% of participants testing positive for at least one drug after not reporting use. For example, based on self-report, cocaine use prevalence was 51.1%, and increased by a factor of 1.6 to a prevalence of 80.0% when adding hair test results to self-report. Younger adults (ages 18–25), black and other/mixed race participants, those reporting "other" sexuality, and those with a college degree were at significantly higher risk for testing positive for drugs not reportedly used. Those who self-reported using more types of drugs were less likely to test positive after not reporting use (adjusted prevalence ratio = 0.53, 95% confidence interval = 0.41-0.68). CONCLUSIONS: We detected underreporting of drug use, particularly cocaine and ketamine. More research is needed to determine whether this is driven by intentional underreporting or unknown exposure through adulterants.